Mesoscale Statistics and Scaling Laws in Planar Elastic Checkerboards - Raghavan, Bharath Venkatesh (2014)
A Master of Science thesis in Mechanical Engineering by Bharath Venkatesh Raghavan entitled, "Mesoscale Statistics and Scaling Laws in Planar Elastic Checkerboards," submitted in May 2014. Thesis advisor is Dr. Shivakumar Ranganathan. Available are both soft and hard copies of the thesis.